Development of an In Vivo Probe to Track SARS-CoV-2 Infection in Rhesus Macaques - Madden, Patrick J.; Arif, Muhammad S.; Becker, Mark E.; McRaven, Michael D.; Carias, Ann M.; Lorenzo-Redondo, Ramon; Xiao, Sixia; Midkiff, Cecily C.; Blair, Robert V.; Potter, Elizabeth Lake; Martin-Sancho, Laura; Dodson, Alan; et al. (Frontiers in Immunology, 2021)
Infection with the novel coronavirus, SARS-CoV-2, results in pneumonia and other respiratory symptoms as well as pathologies at diverse anatomical sites. An outstanding question is whether these diverse pathologies are due to replication of the virus in these anatomical compartments and how and when the virus reaches those sites. To answer these outstanding questions and study the spatiotemporal dynamics of SARS-CoV-2 infection a method for tracking viral spread in vivo is needed. We developed a novel, fluorescently labeled, antibody-based in vivo probe system using the anti-spike monoclonal antibody CR3022 and demonstrated that it could successfully identify sites of SARS-CoV-2 infection in a rhesus macaque model of COVID-19. Our results showed that the fluorescent signal from our antibody-based probe could differentiate whole lungs of macaques infected for 9 days from those infected for 2 or 3 days. Additionally, the probe signal corroborated the frequency and density of infected cells in individual tissue blocks from infected macaques. These results provide proof of concept for the use of in vivo antibody-based probes to study SARS-CoV-2 infection dynamics in rhesus macaques.